Chemoprophylaxis with oral amoxycillin against bacterial endocarditis: when should second doses be administered after dentistry?. Issue 6561 (13th December 1986) - Kumana, C R; Chau, K K; Chau, P Y; Kou, M; Lauder, I
Abstract : The adequacy of serum bactericidal activity after oral amoxycillin given as prophylaxis against infective endocarditis was studied using a double blind randomised protocol in healthy volunteers having dentistry. One hour before their procedure 38 patients received 3 g amoxycillin syrup and 12 received matching placebo. Venous blood samples were drawn before and one and nine hours after dosing and serum amoxycillin concentrations determined using a standard bioassay. Samples containing amoxycillin had inhibitory titres measured against two reference isolates of viridans streptococci known to have caused infective endocarditis. The susceptibility to amoxycillin of one strain was high and the other low, respective minimal bactericidal and inhibitory concentrations being 0.08 and 0.04 mumol/l (0.03 and 0.015 microgram/ml) and 2.74 and 1.37 mumol/l (1 and 0.5 microgram/ml). Amoxycillin was detected in only post-treatment samples of patients given the active drug. There were no significant correlations between one or nine hour drug concentrations and age or physical characteristics, nor was there any relation to preceding food consumption. Correlations between drug concentrations at one and nine hours were weak (r = 0.34; p less than 0.05), but between corresponding drug concentrations and serum inhibitory titres there were consistent correlations (r = 0.46-0.48; p less than 0.005). Against the low susceptibility reference isolate bactericidal amoxycillin concentrations were encountered in only 20 of the 38 nine hour samples (95% confidence limits 34% and 66%). When repeat doses of amoxycillin are indicated after dentistry they should be given about four hours later, not eight hours later as commonly practised.